Auditory brainstem response (ABR) profiling tests as diagnostic support for schizophrenia and adult attention-deficit hyperactivity disorder (ADHD). Issue 3 (14th August 2017) - Juselius Baghdassarian, Eva; Nilsson Markhed, Maria; Lindström, Eva; Nilsson, Björn M; Lewander, Tommy
Abstract : Objective: To evaluate the performances of two auditory brainstem response (ABR) profiling tests as potential biomarkers and diagnostic support for schizophrenia and adult attention-deficit hyperactivity disorder (ADHD), respectively, in an investigator-initiated blinded study design. Method: Male and female patients with schizophrenia ( n =26) and adult ADHD ( n =24) meeting Diagnostic and Statistical Manual of Mental Disorders Fourth Edition (DSM IV) diagnostic criteria and healthy controls ( n =58) comprised the analysis set ( n =108) of the total number of study participants ( n =119). Coded sets of randomized ABR recordings were analysed by an independent party blinded to clinical diagnoses before a joint code-breaking session. Results: The ABR profiling test for schizophrenia identified schizophrenia patients versus controls with a sensitivity of 84.6% and a specificity of 93.1%. The ADHD test identified patients with adult ADHD versus controls with a sensitivity of 87.5% and a specificity of 91.4%. Conclusion: The ABR profiling tests discriminated schizophrenia and ADHD versus healthy controls with high sensitivity and specificity. The methods deserve to be further explored in larger clinical studies including a broad range of psychiatric disorders to determine their utility as potential diagnostic biomarkers.